The development of harmful organisms in corn crops depending on tillage and protection system - Snizhok, O.; Shevchenko, T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. Determine the impact of tillage and protection system on weed species and the development of diseases and pests of corn on grain in the Western Polissia zone. Methods. The research is based on field experiments using methods: visual — to determine phenological phases of growth and development of culture; calculation — to determine the development of diseases, pests, parameters of the structure of crop and harvest capacity of culture; chemical — to determine the content of nutrients in the soil; mathematical and statistical — to assess the reliability of research results; calculation-comparative — for the analysis of economic efficiency. Results. It has been established that tillage has a significant impact on the accumulation of harmful organisms. First of all, this is clearly observed by the number of weeds. For example, with overdeep tillage, the number of weeds was 277.1 pcs./m2, while with soil loosening it was 2.0 times higher (545.6 pcs./m2). The number of weeds, depending on the tillage, when spraying with herbicides, was in the range of 12.5—53.5 pcs./ m2, which is 22.2—10.2 times lower than in the variants without herbicides. A slightly smaller difference in the influence of soil cultivation was monitored on the development and spread of diseases and pests. Conclusions. Under tillage and spraying with herbicides, the number of weeds was 96.8% lower compared to the control. Technical efficiency fungicide Retengo, k.e. (pyraclostrobin, 200 g/l) (0,5 l/ha) against fusarium was at the level of 87.1—90.0%, gray rot — 78.3—80.1% and helminthosporiosis 79.4—81.4%, depending on the tillage. Against them, the main deterrent was still chemical protection. In the variants without an insecticide, the population of maize hairy aphids was 85%. The use of Belt 480 SC, k.s. (flubendiamide 480 g/l) (0.15 l/ha) made it possible to reduce the plant population by the pest by 3.5 times. The 20—22 cm overdeep tillage and 10—12 cm shallow tillage ensured corn yields of 6.90 and 6.28 t/ha of grain, respectively, compared to the 6—8 cm soil loosening (5,36 t/ha). However, the combination of tillage with an intensive protection system allowed to increase the yield to 11.83 and 10.63 t/ha.